æ±‰è¯å°å°¼è¯æ•°å—æˆè¯ä¸€è‡³äº”æ„ä¹‰å¯¹æ¯”åˆ†æž - Deni, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â AbstractProverbs are parts of language used in ancient and modern writings. Chineseâ€™s and Indonesianâ€™s proverbs are indispensable part of the language, and its numbers are quite rich. One of it is the proverb that reflected the meaning of numerals. It is used often to reveal the rank of oneâ€™s life. The writer chose Chineseâ€™s and Indonesian proverbs containing numerals (1, 2, 3, 4 and 5) as the research object. The writer collected and analyzed the meaning of the proverbs were contain numerals from â€œXinhua Chengyu Cidianâ€ and Proverbs Dictionaries, after that compared between Chineseâ€™s and Indonesianâ€™s proverbs. Through comparative and analytical methods, the writer summarizes the meanings, similarities, and differences between Chineseâ€™s and Indonesianâ€™s numeral proverbs. The writer draws the conclusions: from sense of the meanings, the Chineseâ€™s numerals proverbs and the Indonesianâ€™s numeral proverbs containing numbers; "one, two, three, four, five" it has the similarities used to expressed quantities and frequencies. For example; Â Â Â Â Â Â Â Â 'A cage of two birds' and 'ç™¾é‡ŒæŒ‘ä¸€ (BÇŽi lÇ tiÄo yÄ«)'. The writer hopes this thesis can help Chinese teachers to find the right teaching methods in teaching Chineseâ€™s proverbs, help learners more easily to learn Chineseâ€™s proverbs, and improve students' ability to understand and use proverbs.Keywords: Chineseâ€™s Proverbs, Indonesianâ€™s Proverbs, Numeral Proverbs, Comparative Â Â Â Â Â Â Â  Â AnalysisÂ